Methicillin-resistant Staphylococcus aureus-induced thrombo-inflammatory response is reduced with timely antibiotic administration - Franks, Zechariah; Campbell, Robert A.; de Abreu, Adriana Vieira; Holloway, Jeffrey T.; Marvin, James E.; Kraemer, Bjoern F.; Zimmerman, Guy A.; Weyrich, Andrew S.; Rondina, Matthew T. (Thrombosis and Haemostasis, 2013)
Methicillin-resistant Staphylococcus aureus (MRSA) induces a prothrombotic and pro-inflammatory milieu. Although timely antibiotic administration in MRSA sepsis may improve outcomes by arresting bacterial growth, the effects of antibiotics on mitigating injurious thrombo-inflammatory cellular responses remains unexplored. Using a newly developed human whole blood model and an in vivo mouse model of MRSA infection, we examined how antibiotics inhibit MRSA induced thrombo-inflammatory pathways. Human whole blood was inoculated with MRSA. Thrombin generation and inflammatory cytokine synthesis was measured in the presence or absence of linezolid and vancomycin. C57BL/6 mice were injected with MRSA and the effect of vancomycin administration was examined. MRSA accelerated thrombin generation in a time- and concentration-dependent manner and induced the release of cytokines, including interleukin (IL)-6, IL-8, and monocyte chemotactic protein (MCP)-1. The increase in thrombin generation and inflammatory responses was mediated through the synthesis of tissue factor and cytokines, respectively, and the release of microparticles. The early administration of antibiotics restored normal thrombin generation patterns and significantly reduced the synthesis of cytokines. In contrast, when antibiotic administration was delayed, thrombin generation and cytokine synthesis were not significantly reduced. In mice infected with MRSA, early antibiotic administration reduced thrombin anti-thrombin complexes and cytokine synthesis, whereas delayed antibiotic administration did not. These data provide novel mechanistic evidence of the importance of prompt antibiotic administration in infectious syndromes.
Keywords: Thrombin; tissue factor; cytokines; methicillin-resistant Staphylococcus aureus; antibiotics